The Antiaggregating and Antithrombotic Activity of Clopidogrel Is Potentiated by Aspirin in Several Experimental Models in the Rabbit - Herbert, Jean-Marc; Dol, Frédérique; Bernat, André; Falotico, Robert; Lalé, Alain; Savi, Pierre (Thrombosis and Haemostasis, 1998)
It is unknown whether the addition of aspirin might increase both the efficacy and the potency of clopidogrel, a potent and selective ADP blocker. For that purpose, the efficacy of clopidogrel (1–20 mg/kg, p.o.) administered orally to rabbits alone or in combination with aspirin (0.1–10 mg/kg, p.o.) was determined in several experimental models. A potent synergistic effect of the clopidogrel/aspirin association was demonstrated with regard to collagen-induced platelet aggregation measured ex vivo. Similarly, aspirin potentiated the antithrombotic activity of clopidogrel measured with regard to experimental thrombosis induced by a silk thread or on stents placed in an arteriovenous shunt, thrombus formation following electrical stimulation of the rabbit carotid artery and with regard to 111In-labeled platelet deposition on a stent implanted in an arteriovenous shunt or on the subendothelium following air drying injury of the rabbit carotid artery. A similar potentiating effect of aspirin was obtained with regard to myointimal proliferation (restenosis) in the femoral arteries of atherosclerotic rabbits which occurred as a consequence of stent placement. The clopidogrel/aspirin combination showed only additive-type effects on bleeding time prolongation induced by ear transection in the rabbit, therefore showing that combined inhibition of cyclooxygenase and ADP‘s effects provide a marked enhanced antithrombotic efficacy. Such a combination may provide substantial protection against platelet aggregation leading to thrombotic occlusion at sites of endothelial injuries and coronary artery stenosis in humans.